How does residency program reputation influence American shoulder and elbow surgeons fellowship match results? - Alexander Jurayj, BA; Taylor Timoteo, DO; Julio Nerys-Figueroa, BS; Johnny Kasto, MD; Jared M. Mahylis, MD; Stephanie J. Muh, MD (JSES Reviews, Reports, and Techniques)
Background: Postresidency training is becoming increasingly common among orthopedic surgeons, with shoulder and elbow surgery growing as a desired subspeciality. There is limited data evaluating how the reputation of an applicants’ orthopedic residency influences the outcome of the shoulder and elbow fellowship match. The purpose of this study was to determine if applicants from residencies with better reputation have more favorable odds during the match process compared to applicants from residencies with a less prestigious reputation. Methods: Residency reputation was determined using the 2023 Doximity residency ranking. These residency programs were then divided into 5 tiers (with tier 1 being the highest ranked and tier 5 being the lowest). Fellowship match data was obtained via San Francisco match from 2016 to 2023. Unmatched applicants, international graduates, and applicants without residency information were excluded. Applicants from 2016 to 2017 were excluded due to incomplete match data. Statistical analysis included descriptive statistics, Chi-square, analysis of variance, and nonparametric analysis. Results: There was a statistically significant difference with residency tier and average matched rank by fellowship program (P < .001). Applicants from tiers 1, 2, and 3 were more likely to be ranked higher compared to applicants from tiers 4 and 5. Applicants from tier 1 programs sent fewer applications and received a greater proportion of interview offers compared to applicants from tiers 3, 4, and 5 (P < .001). Tier 1 applicants were significantly more likely to be “ranked to match” compared to all remaining applicants (P < .001). There was no significant difference associated with residency tier and match position on the applicant’s rank list. However, applicants from tier 1 programs were significantly more likely to match at their top 2 desired programs, compared to applicants from tiers 3, 4, and 5 (P = .029, P = .023, P = .012). Tier 2 applicants were more likely to match at one of their top 2 programs compared to tier 4 and 5 applicants (P = .045, P = .023). Conclusion: Applicants from higher tier residencies are more likely to be ranked higher by shoulder and elbow fellowship programs compared to applicants from lower-tier residencies. Tiers 1, 2, and 3 are ranked approximately equally, while tiers 4 and 5 are ranked significantly lower. There was no association noted between residency tier and applicant match rank; however, applicants from higher-tier residencies were far more likely to match at their top fellowship programs compared to applicants from lower-tier residencies.